Climatically controlled lacustrine clinoforms: Theory and modelling results. (16th July 2019) - Zhang, Jinyu; Olariu, Cornel; Steel, Ronald; Kim, Wonsuck
Abstract: Lacustrine basins and their deposits are good paleoclimate recorders and contain rich energy resources. Shelf‐margin clinoforms do exist in deep lacustrine basins, but with striking differences from those in deep marine basins, caused by a correlation between the river‐derived sediment supply and the lake level. This study uses empirical relationships to calculate the water and sediment discharge from rivers and coeval lake level during wet–dry cycles at 10 s of ky time scale. Sediment supply and lake‐level changes are used for a stratigraphic forward model to understand how lacustrine clinoforms develop under different climate conditions. The results show that both wet and dry cycles can be associated with thick deep‐water fan deposits, supporting the existing climate‐driven lacustrine model proposed based on field data (e.g. Neogene Pannonian Basin and Eocene Uinta Basin). The wet period with high sediment supply and rising lake level creates the highly aggradational shelf, progradational slope and thick bottomset deposits. This is contrary from marine basin settings where the presence of rising shelf‐margin trajectory commonly indicates limited deep‐water fan deposits. This work suggests marine‐based stratigraphic models cannot be directly applied to lacustrine basins.